Live-attenuated Mycobacterium tuberculosis vaccine MTBVAC versus BCG in adults and neonates: a randomised controlled, double-blind dose-escalation trial. Issue 9 (September 2019) - Tameris, Michele; Mearns, Helen; Penn-Nicholson, Adam; Gregg, Yolande; Bilek, Nicole; Mabwe, Simbarashe; Geldenhuys, Hennie; Shenje, Justin; Luabeya, Angelique Kany Kany; Murillo, Ingrid; Doce, Juana; Aguilo, Nacho; et al.
Summary: Background: Infants are a key target population for new tuberculosis vaccines. We assessed the safety and immunogenicity of the live-attenuated Mycobacterium tuberculosis vaccine candidate MTBVAC in adults and infants in a region where transmission of tuberculosis is very high. Methods: We did a randomised, double-blind, BCG-controlled, dose-escalation trial at the South African Tuberculosis Vaccine Initiative site near Cape Town, South Africa. Healthy adult community volunteers who were aged 18–50 years, had received BCG vaccination as infants, were HIV negative, had negative interferon-γ release assay (IGRA) results, and had no personal history of tuberculosis or current household contact with someone with tuberculosis were enrolled in a safety cohort. Infants born to HIV-negative women with no personal history of tuberculosis or current household contact with a person with tuberculosis and who were 96 h old or younger, generally healthy, and had not yet received routine BCG vaccination were enrolled in a separate infant cohort. Eligible adults were randomly assigned (1:1) to receive either BCG Vaccine SSI (5 × 10 5 colony forming units [CFU] of Danish strain 1331 in 0·1 mL diluent) or MTBVAC (5 × 10 5 CFU in 0·1 mL) intradermally in the deltoid region of the arm. After favourable review of 28-day reactogenicity and safety data in the adult cohort, infants were randomly assigned (1:3) to receive either BCG Vaccine SSI (2·5 × 10 5 CFU in 0·05 mL diluent) or MTBVAC in three sequential cohorts of increasing MTBVAC dose (2·5 × 10 3 CFU, 2·5 × 10 4 CFU, and 2·5 × 10 5 CFU in 0·05 mL) intradermally in the deltoid region of the arm. QuantiFERON-TB Gold In-Tube IGRA was done on days 180 and 360. For both randomisations, a pre-prepared block randomisation schedule was used. Participants (and their parents or guardians in the case of infant participants), investigators, and other clinical and laboratory staff were masked to intervention allocation. The primary outcomes, which were all measured in the infant cohort, were solicited and unsolicited local adverse events and serious adverse events until day 360; non-serious systemic adverse events until day 28 and vaccine-specific CD4 and CD8 T-cell responses on days 7, 28, 70, 180, and 360. Secondary outcomes measured in adults were local injection-site and systemic reactions and haematology and biochemistry at study day 7 and 28. Safety analyses and immunogenicity analyses were done in all participants who received a dose of vaccine. This trial is registered with ClinicalTrials.gov, number NCT02729571 . Findings: Between Sept 29, 2015, and Nov 16, 2015, 62 adults were screened and 18 were enrolled and randomly assigned, nine each to the BCG and MTBVAC groups. Between Feb 12, 2016, and Sept 21, 2016, 36 infants were randomly assigned—eight to the BCG group, nine to the 2·5 × 10 3 CFU MTBVAC group, nine to the 2·5 × 10 4 CFU group, and ten to the 2·5 × 10 5 CFU group. Mild injection-site reactions occurred only in infants in the BCG and the 2·5 × 10 5 CFU MTBVAC group, with no evidence of local or regional injection-site complications. Systemic adverse events were evenly distributed across BCG and MTBVAC dose groups, and were mostly mild in severity. Eight serious adverse events were reported in seven vaccine recipients (one adult MTBVAC recipient, one infant BCG recipient, one infant in the 2·5 × 10 3 CFU MTBVAC group, two in the 2·5 × 10 4 CFU MTBVAC group, and two in the 2·5 × 10 5 CFU MTBVAC group), including one infant in the 2·5 × 10 3 CFU MTBVAC group treated for unconfirmed tuberculosis and one in the 2·5 × 10 5 CFU MTBVAC group treated for unlikely tuberculosis. One infant died as a result of possible viral pneumonia. Vaccination with all MTBVAC doses induced durable antigen-specific T-helper-1 cytokine-expressing CD4 cell responses in infants that peaked 70 days after vaccination and were detectable 360 days after vaccination. For the highest MTBVAC dose (ie, 2·5 × 10 5 CFU), these responses exceeded responses induced by an equivalent dose of the BCG vaccine up to 360 days after vaccination. Dose-related IGRA conversion was noted in three (38%) of eight infants in the 2·5 × 10 3 CFU MTBVAC group, six (75%) of eight in the 2·5 × 10 4 CFU MTBVAC group, and seven (78%) of nine in the 2·5 × 10 5 CFU MTBVAC group at day 180, compared with none of seven infants in the BCG group. By day 360, IGRA reversion had occurred in all three infants (100%) in the 2·5 × 10 3 CFU MTBVAC group, four (67%) of the six in the 2·5 × 10 4 CFU MTBVAC group, and three (43%) of the seven in the 2·5 × 10 5 CFU MTBVAC group. Interpretation: MTBVAC had acceptable reactogenicity, and induced a durable CD4 cell response in infants. The evidence of immunogenicity supports progression of MTBVAC into larger safety and efficacy trials, but also confounds interpretation of tests for M tuberculosis infection, highlighting the need for stringent endpoint definition. Funding: Norwegian Agency for Development Cooperation, TuBerculosis Vaccine Initiative, UK Department for International Development, and Biofabri.